2017
DOI: 10.1007/s10072-017-2854-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with telmisartan, a long-acting angiotensin II receptor blocker, prevents migraine attacks in Japanese non-responders to lomerizine

Abstract: Lomerizine, calcium channel blocker, is the most used medication for migraine prophylaxis in Japan. The effectiveness of this drug is reported as 50-75%. Telmisartan is angiotensin II receptor blockers which plasma half-life is 24 h. We examined whether telmisartan has preventative benefits in lomerizine non-responsive migraineurs. Lomerizine non-responders received telmisartan (20 mg/day) for 3 months after the investigation period of 3 months. Blood pressure, frequency of headache days/month, headache severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, patients treated with ARBs for reasons other than migraine showed a 31% lower incidence of headache during the treatment with these drugs 33 . The uniqueness of candesartan compared with other ARBs might be related to the selectivity, half-life, and tolerability 3 ; however, studies on other ARBs are even more scarce 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients treated with ARBs for reasons other than migraine showed a 31% lower incidence of headache during the treatment with these drugs 33 . The uniqueness of candesartan compared with other ARBs might be related to the selectivity, half-life, and tolerability 3 ; however, studies on other ARBs are even more scarce 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, based on a chemical library that consisted of FDA‐approved commercial drugs, we found that lomerizine 2HCl exhibited potent anticancer activity against CRC cells. It has been reported that lomerizine 2HCl can decrease the frequency of migraine headaches with an effectiveness of 50%–75% 22 . However, there have been no studies to investigate the anticancer effects of lomerizine 2HCl.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lomerizine 2HCl can decrease the frequency of migraine headaches with an effectiveness of 50%–75%. 22 However, there have been no studies to investigate the anticancer effects of lomerizine 2HCl. Thus, we provide the first line of evidence showing the suppressive effects of lomerizine 2HCl on cell growth, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension has been identified as one of the most important factors of chronic transformation of episodic migraine and increases the cerebrovascular and cardiovascular risk of migraine patients [76]. Telmisartan, a long-acting angiotensin II receptor blocker, has preventative benefits in non-responsive migraineurs [77]. OnabotulinumtoxinA, an effective treatment of chronic migraine, presents an increase of therapy efficacy and a progressive trend of "first-time response" [78].…”
mentioning
confidence: 99%